2006
DOI: 10.1124/dmd.106.010405
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Stereoselective Metabolism of Cephalexin by Exogenous Transfection of Oligopeptide Transporter PEPT1

Abstract: Gastrointestinal absorption of the beta-lactam antibiotic cephalexin (CEX) is highly stereoselective: l- and d-CEX are both taken up by intestinal epithelial cells through the brush-border membrane, most likely via oligopeptide transporter PEPT1, but l-CEX is not found in serum or urine after administration p.o. because of its rapid intestinal metabolism, whereas d-CEX is well absorbed in the unchanged form. We examined the contribution of PEPT1 to the stereoselective uptake and metabolism of CEX. We observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…[266,267]) have been carried out on SLC15 [268] members (previously known as PEPT1 and PEPT2), and responsible e.g. for the intestinal uptake of penicillins [269] and cepaholsporins [270,271].…”
Section: The Importance Of Qsars (Quantitative Structure-activity Relmentioning
confidence: 99%
“…[266,267]) have been carried out on SLC15 [268] members (previously known as PEPT1 and PEPT2), and responsible e.g. for the intestinal uptake of penicillins [269] and cepaholsporins [270,271].…”
Section: The Importance Of Qsars (Quantitative Structure-activity Relmentioning
confidence: 99%
“…13,16,17) These observations and the fact that a metabolite of L-cephalexin, 7-ADCA, was detected immediately after oral dosing 18) imply that PEPT1 itself may mediate L-cephalexin hydrolysis, although to date, only we 13) have suggested that hydrolytic enzyme activity may be associated with PEPT1. In the present study using budded baculovirus, which expresses PEPT1, but not any endogenous mammalian enzyme, PEPT1-mediated transport of L-cephalexin was clearly observed, since substantial amount of intact Lcephalexin was detected in PEPT1-expressing budded baculovirus (Fig.…”
Section: ) L-mentioning
confidence: 89%
“…13) Indeed, hydrolysis of L-cephalexin was markedly increased by exogenous transfection of PEPT1 gene into cultured cell lines, and metabolism of cephalexin was observed even in membrane-permeabilized cells expressing PEPT1, in which intracellular accumulation of L-cephalexin was negligible. 13) This observation may imply that L-cephalexin hydrolysis is mediated by PEPT1 itself, although possible involvement of endogenous peptidases cannot be excluded, because these experimental systems utilized mammalian cells.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations